2017
DOI: 10.1007/s12665-017-6409-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of UAV photogrammetry for the multi-temporal estimation of surface extent and volumetric excavation in the Sa Pigada Bianca open-pit mine, Sardinia, Italy

Abstract: In open-pit mines, monitoring of topographic and volumetric changes through time is found to be of great importance to support excavation stages and to plan rehabilitation strategies. In this work, we describe a geomatic approach to assess changes in surface mine extent and to quantify excavated volume in the Sa Pigada open-pit mine, Sardinia, Italy. We performed two drone-based photogrammetric surveys in 2013 and 2015, and by means of the Structure from Motion (SfM) technique, we obtained related 3D dense poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 34 publications
1
53
0
2
Order By: Relevance
“…The conducted study was inspired by the paper of Esposito et al (2017), who outlined the possibilities of using UAV technology for monitoring open pit mines, especially recording the changes taking place and performing cubature calculations on the basis of the point cloud. In addition, this paper aimed to further the research done by Slater et al (2010) concerning the possibility of using VR for a more immersive exploration of 3D geovisualisation in the VR FPV mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conducted study was inspired by the paper of Esposito et al (2017), who outlined the possibilities of using UAV technology for monitoring open pit mines, especially recording the changes taking place and performing cubature calculations on the basis of the point cloud. In addition, this paper aimed to further the research done by Slater et al (2010) concerning the possibility of using VR for a more immersive exploration of 3D geovisualisation in the VR FPV mode.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of using the UAV technology to monitor open pit mines, especially with the purpose of tracking the occurring changes and making cubature calculations on the basis of the point cloud, has been described, among others, by Esposito et al (2017) based on the example of Sa Pigada Bianda in Sardinia. Due to the technological development of the miniaturisation process and the decreasing production costs of the components used in UAV construction, the vehicles are becoming more and more popular as surveying platforms in geophysical research.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 shows the trend of increasing volumetric estimations as a function of grid size. Esposito et al (2017) performed a sensitivity analysis of the cell size on the volumetric estimations of an excavated mine and found that the estimated volume increased with cell size, and then used 50 cm as optimal cell resolution. The effect of grid size on volumetric assessments was expected.…”
Section: Volumetric Change Estimationsmentioning
confidence: 99%
“…where σ 1 (d) and σ 2 (d) are calculated as the standard deviations of elevations of the subset of points (I, J) in the cylinder, and n 1 and n 2 are the number of subset of points in the cylinder (see 'Elevation change calculation', above) (Lague et al, 2013;Esposito et al, 2017).…”
Section: Level Of Detectionmentioning
confidence: 99%
See 1 more Smart Citation